Currículo e diversidade cultural indígena no Amazonas: representações da Escola Tenharin em Humaitá e Manicoré - Nogueira, Eulina Maria Leite (2015)
The present work approaches the Tenharin People indigenous school thematic, located at the banks of the BR-230 highway, known as Transamazônica. The research was conducted along the Tenharin indigenous schools along the highway, summing a two schools in Humaitá and six in Manicoré, in the Amazon state. The goal was to comprehend the meaning around the school attributed by the indigenous teachers who act in theses schools and their resume implications. The goals that originated the research were: rebuild the historical path of Indigenous School Education; identify the formation politics of indigenous teachers in Humaitá and Manicoré; comprehend the historical process of the Tenharin People presence in Amazonas; and identify the social representation of teachers in relation to the school. The applied methodology has qualitative terms; for this purpose, the utilized sources had documental character, with institutional documents analysis and works that sustain the theoretical basis of research on indigenous teachers from the Tenharin People, protagonists of this study. Evocation technique and interviews were utilized as research tools. The data analysis was guided by a theoretical triangulation: Resume Theory, Social Representation Theory and Critical Theory